1985
DOI: 10.1073/pnas.82.17.5715
|View full text |Cite
|
Sign up to set email alerts
|

Sterol control of the phosphatidylethanolamine-phosphatidylcholine conversion in the yeast mutant GL7.

Abstract: The relatively slow growth rate of the yeast mutant GL7, a sterol auxotroph, on medium containing cholesterol is markedly accelerated by supplementation with small amounts of ergosterol. Under these conditions (sterol synergism) cellular phospholipid synthesis is enhanced. We now find that one of the ergosterol-stimulated processes is the methylation of phosphatidylethanolamine to phosphatidylcholine. This is shown by comparing methyltransferase activities of membrane preparations derived from cells grown on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 20 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…This will promote more effective interaction between the phospholipid acyl chains and the sterol a-face (Buttke and Bloch 1980). Examining the transmethylation pathway for the synthesis of phosphatidy1chol-ine, Kawasaki et al (1985) observed an ergosterol-specific promotion of enzyme activity. They found that GL 7 cells grown on ergosterol or ergosterol/cholesterol (1: 3) mixtures, incorporate several times more 3H from [methyl-3Hj methionine into phosphatidylcholine than cells that have been raised on cholesterol alone.…”
Section: Studies Using Sterol Auxotrophsmentioning
confidence: 96%
“…This will promote more effective interaction between the phospholipid acyl chains and the sterol a-face (Buttke and Bloch 1980). Examining the transmethylation pathway for the synthesis of phosphatidy1chol-ine, Kawasaki et al (1985) observed an ergosterol-specific promotion of enzyme activity. They found that GL 7 cells grown on ergosterol or ergosterol/cholesterol (1: 3) mixtures, incorporate several times more 3H from [methyl-3Hj methionine into phosphatidylcholine than cells that have been raised on cholesterol alone.…”
Section: Studies Using Sterol Auxotrophsmentioning
confidence: 96%
“…Phosphotyrosine was not detected. The membrane fraction of yeast has been shown to possess protein kinase activity (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of 12 different sterols to affect (i) cell growth, (ii) lipid head group composition, (iii) the order parameter of the acyl chains, and (iv) the phase equilibria of in vivo lipid mixtures was studied. The following two effects were observed with respect to cell growth: (i) with a given acyl chain composition of the membrane lipids, growth was stimulated, unaffected, reduced, or completely inhibited (lysis), depending on the sterol structure; and (ii) the effect of a certain sterol depended on the acyl chain composition (most striking for epicoprostanol, cholest-4-en-3-one, and cholest-5-en-.3-one, which stimulated growth with saturated acyl chains but caused lysis with unsaturated chains (8,18,26), Of the membrane physical properties affected by sterols, the most commonly investigated are the gel-to-liquid crystalline phase transition temperature (Tm) of the lipids (11,17,20), the order parameter of the lipid acyl chains (17,30,32), and the permeability of the membranes or the derived lipids (1, 10, 12). Recently, studies have also been performed on the ability of some sterols to induce the transition between a lamellar phase and a nonlamellar phase, most often a reversed hexagonal (HI,) phase, in lipid-water model systems (7,15,25 …”
mentioning
confidence: 99%
“…However, more specific functions of some sterols have recently been observed for two organisms auxotrophic for sterols, Mycoplasma capricolum and Saccharomyces cerevisiae. Addition of minor concentrations of a certain sterol to a growth medium already containing another sterol in a manifold higher concentration enhances the rate of important metabolic processes (8,18,26), Of the membrane physical properties affected by sterols, the most commonly investigated are the gel-to-liquid crystalline phase transition temperature (Tm) of the lipids (11,17,20), the order parameter of the lipid acyl chains (17,30,32), and the permeability of the membranes or the derived lipids (1,10,12). Recently, studies have also been performed on the ability of some sterols to induce the transition between a lamellar phase and a nonlamellar phase, most often a reversed hexagonal (HI,) phase, in lipid-water model systems (7,15,25).…”
mentioning
confidence: 99%